The reduction of hippocampal volume in Parkinson's disease - Říha, Pavel; Brabenec, Luboš; Mareček, Radek; Rektor, Ivan; Rektorová, Irena (Journal of neural transmission (Vienna, Austria, 2022)
The volume of the hippocampus decreases more slowly than the volume of the cortex during normal aging. We explored changes in the hippocampus-to-cortex volume (HV:CTV) ratio with increasing age in non-demented Parkinson's disease (PD) patients as compared to healthy controls (HC). We also evaluated the association between the HV:CTV ratio and cognitive outcomes. Altogether 130 participants without dementia aged 51-88 years were consecutively enrolled, including 54 PD patients (mean age 67, standard deviation (SD) 8 years) and 76 HC (mean age 69, SD 7 years). All participants underwent structural magnetic resonance examination and psychological evaluation. Hippocampal and cortex volumes were determined from T1 and FLAIR scans using FreeSurfer software, and the HV:CTV ratio was calculated. Regression lines for age-dependence of the HV:CTV ratio for PD and HC groups were calculated. We further assessed the association between the HV:CTV ratio and cognitive tests examining hippocampus-related cognitive functions. PD patients and age-matched HC showed a significant difference in age-dependence of HV:CTV ratio (p value = 0.012), with a decreasing slope in PD and increasing slope in HC. In the PD group, a significant correlation (R = 0.561, p = 0.024) was observed between the HV:CTV ratio and the Digit Symbol-Coding test. The reduction of HV:CTV ratio is accelerated in pathological aging due to PD pathology. The HV:CTV ratio was associated with impaired processing speed, i.e., the cognitive function that is linked to subcortical alterations of both associated basal ganglia circuitry and the hippocampus.
Keywords: Neuropsychological Tests; Parkinson’s disease; Hippocampus; neuropsychologické testy; Atrophy; Aging; Magnetic Resonance Imaging; Aged; lidé; Parkinson Disease; senioři; Parkinsonova nemoc; Hippocampus-to-cortex volume ratio; Processing speed; magnetická rezonanční tomografie; hipokampus; Humans; atrofie